Formulation of Tablets Containing Mesoporous Silica Nanoparticles Loaded with Pramipexole - Voycheva, Christina; Popova, Teodora; Slavkova, Marta; Tzankova, Diana; Tzankov, Borislav (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: In order to develop final pharmaceutical product, the mesoporous silica particles loaded with pramipexole should be further formulated in the applicable solid dosage forms - tablets. The aim of the study was preparation of tablets containing MCM-41 particles loaded with pramipexole. Materials and Methods: Mesoporous silica particles empty and loaded were subjected to dynamic light scattering analysis (DLS), transmission electron microscopy analysis (TEM) and infrared spectroscopy (IR). Modification of drug release was achieved by further formation of double chitosan/alginate coating. The formulation of tablets was made using diluents, a binder, disintegrate, glidant and a lubricant as well as the silica particles loaded with pramipexole. Flow ability and compressibility of the initial powder mixtures and were examined by tapping method calculating the Carr index and Hausner ratio. Direct compression method was used for tablet preparation. The crushing strength, friability of the tablets and their disintegration time were determined. In-vitro release profiles showed that tablet form influenced first stages of pramipexole release in both pH values, used in the study (pH 1.2 and pH 6.8). Results: Final pharmaceutical dosage form tablets were successfully formulated with pramipexole loaded MCM-41. No change in mesopourous structure and other characterisic properties of used nanoparticles was observed. Improved profile in first release stage were observed. Conclusion: The use of polymers such as chitosan and sodium alginate in silica particles modification successfully delay the process of releasing pramipexole from MCM-41.
Keywords: MCM-41; Pramipexole; Chitosan; Sodium alginate; Modified release